2017
DOI: 10.15642/jrpm.2017.2.2.167-175
|View full text |Cite
|
Sign up to set email alerts
|

Self Efficacy Terhadap Matematika Melalui Pendekatan Aptitude Treatment Interaction

Abstract: This study aims to determine differences in mathematics self-efficacy among students who learn to use the Aptitude Treatment Interaction (ATI) approach with students receiving conventional learning. This study is a quasiexperimental research, where teachers who play a direct role in the learning process and there researcher as an observer. Subjects in this study were 32 students on grade VIII SMP Negeri 2 Bangkinang Pekanbaru. Data collected by aptitude tests, observation, test result, and questionnaire. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…This can be seen based on the average post-test score of the experimental class which is higher than the average post-test score of the control class (Bagindo & Yulia, 2019). The results of research at SMPN 2 Bangkinang Pekanbaru in class VIII revealed that the use of the aptitude treatment interaction model in learning mathematics had a significant optimization of learning outcomes and this was obtained through adjustments between the treatment given and the differences in students' abilities, it was also found that good preparation the application of the aptitude treatment interaction model is needed so that teaching and learning activities can run effectively and meaningfully (Fitri, 2017). The results of research at SMPN 1 Tarogong Kidul in class VIII students reveal that although the aptitude treatment interaction model has been proven to be able to increase students' mathematical understanding, teachers are expected to be able to provide more stimulus to students by giving questions so that their mathematical understanding abilities can increase (Pamungkas & Afriansyah, 2017).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…This can be seen based on the average post-test score of the experimental class which is higher than the average post-test score of the control class (Bagindo & Yulia, 2019). The results of research at SMPN 2 Bangkinang Pekanbaru in class VIII revealed that the use of the aptitude treatment interaction model in learning mathematics had a significant optimization of learning outcomes and this was obtained through adjustments between the treatment given and the differences in students' abilities, it was also found that good preparation the application of the aptitude treatment interaction model is needed so that teaching and learning activities can run effectively and meaningfully (Fitri, 2017). The results of research at SMPN 1 Tarogong Kidul in class VIII students reveal that although the aptitude treatment interaction model has been proven to be able to increase students' mathematical understanding, teachers are expected to be able to provide more stimulus to students by giving questions so that their mathematical understanding abilities can increase (Pamungkas & Afriansyah, 2017).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…It is one of the effective learning models applied especially to the system of linear equations in vocational secondary schools because it focuses on providing effective solutions. The different treatment methods and the treatment given are adapted to the characteristics of each student group, so this grouping is expected to produce optimal learning outcomes (Fitri, 2017). The learning design developed in this study includes designing mathematical learning on systems of linear equations by applying the aptitude treatment interaction model.…”
Section: Resultsmentioning
confidence: 99%
“…In its application, ATI places greater emphasis on providing different treatments in learning; the treatment given is adjusted to the characteristics of each group of students, and with this grouping, it is hoped that it will produce optimal learning outcomes (Fitri, 2017). A teacher who applies the ATI model will try to find a treatment method that suits the differences (abilities) in students' abilities; namely, the treatment is applied optimally to students with different ability levels (Pamungkas & Afriansyah, 2017).…”
Section: Aptitude Treatment Interaction (Ati)mentioning
confidence: 99%
“…(Sumarni et al, 2019). The examples of those related studies are Self-Efficacy towards mathematics through the Aptitude Treatment Interaction approach (Lestari et al, 2019), the effectiveness of the Aptitude Treatment Interaction model in improving learning styles and learning outcomes (Sagala, Umam, Thahir, Saregar, & Wardani, 2019), the development of mathematical learning tools with the Aptitude Treatment Interaction model, the application of the Aptitude Treatment Interaction to the material of space building (Lestari 2018;Fitri 2017;Preacher & Sterba 2019;Kusumawati 2016;Saregar et al 2017;Nugroho, 2018). Mathematical creative thinking abilities of students have been extensively studied before, including creative thinking abilities that are influenced by the project based learning stem model (Prastowo et al, 2019), abilities that are influenced by Problem Based Learning models, the relationship of creative thinking and critical thinking of students, increasing the ability to think creatively with ethnomatematics-based on mathematical.…”
Section: Figure 1percentage Of Correct Answers Of Indonesian Studentmentioning
confidence: 99%